Raumkonstruktionen = Spatial Constructions Digital Humanities und die 'Messbarkeit' des NS-Regimes | The Digital Humanities And The 'Measurability' Of The Nazi Regime - Němec, Richard (Journal für Kultur und Geschichte der Deutschen im östlichen Europa (JKGE) / Journal for Culture and History of the Germans in Eastern Europe, 2021)
During National Socialist occupation in World War II, Eastern Europe was measured, surveyed, and planned anew. Alongside the actors, practices, and technology involved in this process, this volume presents results from the fields of regional and urban planning, and architectural research, inquiring in particular into the possibility of 'measuring,' documenting, and presenting the Nazi occupation regime using digital methods of analysis.